An Analysis Code Switching Found in “Bestie” Series Season - Gede Rendy Adnyana Putra; I Komang Sulatra (Universitas Islam Negeri Palopo, 2025)
This study aims to explore the use of code-switching in Bestie Series Season 1, with a focus on how bilingual speakers alternate between Indonesian and English in informal conversations. The data were sourced from eight episodes of the series, which features spontaneous, bilingual dialogues. Using a descriptive qualitative approach, the conversations were transcribed and analyzed to identify types of code-switching. The analysis was guided by Poplack, (2001) classification, which includes intra-sentential, inter-sentential, and tag-switching. The findings reveal that intra-sentential code-switching is the most frequently used (58.75%), followed by inter-sentential (30%) and tag-switching (11.25%). These results suggest that code-switching in the series is used strategically not only to express emotions and reinforce identity, but also to increase clarity and engagement. In the context of informal digital media, code-switching serves as a flexible and expressive communication tool that reflects the dynamic nature of bilingual interaction.